PENDIDIKAN PESANTREN DAN KETIMPANGAN PENDAPATAN (BUKTI DATA PANEL DI ACEH) - Khairul Amri; Muhammad Adnan; Julianty (Majelis Pendidikan Aceh, 2021)
This study analyzes income inequality using Islamic boarding school education as predictor variables. The Islamic boarding school education is measured using two dimensions, namely the pesantren and santri. Using panel data from 23 regencies in Aceh during the 2010-2017 period, the analysis model used is panel regression with the fixed-effect approach and the Granger causality test. Research reveals that the number of pesantren and santri significantly increases income inequality. The more the pesantren and santri, the higher the income inequality. One-way causality exists from income inequality to the number of pesantren and from the number of santri to pesantren.